Muscle involvement in leprosy: study of the anterior tibial muscle in 40 patients - LINEU CESAR WERNECK; HÉLIO A.G. TEIVE; ROSANA HERMINIA SCOLA (Arquivos de Neuro-Psiquiatria)
The involvement of skeletal striated muscle in leprosy is considered secondary due to peripheral neuropathy, but some studies point it to a primary muscle lesion. In order to investigate the muscle involvement in leprosy, we studied 40 patients (lepromatous 23, tuberculoid 13, borderline 2 and indeterminate 2). The motor nerve conduction of the peroneal nerves had a reduction of the velocity, decreased compound muscle action potential and sometimes absence of potentials. The electromyographic study of the anterior tibial muscle showed signs of recent and chronic denervation in 77.5% of the cases and no myopathic potentials. The anterior tibial muscle biopsy revealed denervation in 45% of the cases, interstitial inflammatory myopathy in 30% and mixed (myopathic and neuropathic) pattern in 12.5%. Acid fast bacillus was detected in 25% of the cases, always in the interstitial tissue. Inflammatory reaction was present in the interstitial space and in patients with the lepromatous type. The histological findings clearly defined the presence of the so-called "Leprous Interstitial Myositis" on the top of denervation signs.